Valorization of plant extracts by encapsulation in lipid nanosystems for application as potential insecticides - Lopes, Ana I. F. (2019)
Plants have been used for centuries to treat diseases and are considered an important source of new antimicrobial agents. Plant extracts can be obtained and their composition determined, being widely employed in the pharmaceutical and cosmetic industries. A less explored and potential application is the use as green insecticides/insect repellents, as an alternative to current pesticides. Despite the desirable properties, many of the isolated components (phytochemicals) present limitations on their use, due to high volatility and easy degradation when exposed to air. Nanoencapsulation techniques arise as promising strategies to allow the preservation and controlled release of plant extracts. In this work, a series of plant materials, Tamus communis L., Tagetes patula L. and Ruta graveolens L., were subjected to Soxhlet extraction using various solvents and times of extraction. The extracts obtained were submitted to biological studies, to assess their potential against the insect cell line Sf9. Encapsulation assays in lipid nanosystems were carried out, with encapsulation efficiencies higher than 70%.